Prevalence and Demographic Patterns of Diabetic Retinopathy, Retinal Vein Occlusion, and Age-Related Macular Degeneration in Eastern India: An Epidemiological Study - Sinha, Bibhuti Prassan; Anand, Abhishek; Kumar, Aniket; Sinha, Shivani; Yadav, Nishita (International Journal of Retina, 2025)
Purpose: To elucidate the epidemiology, clinical characteristics, and treatment outcomes of retinal diseases in Eastern India. Methodology: This prospective observational study was conducted at a tertiary care hospital from August 2021 to December 2022. Adult patients (≥18 years) diagnosed with diabetic retinopathy (DR), retinal vein occlusion (RVO), or age-related macular degeneration (ARMD) were enrolled after obtaining informed consent. Comprehensive data collection, including demographic information, clinical characteristics, and treatment outcomes, was conducted. Data were analyzed using descriptive and inferential statistical methods. Results: The study cohort (N=812) exhibited a predominance of DR (60.84%, 95% CI: 57.4-64.2%), followed by branch retinal vein occlusion (BRVO, 18.72%, 95% CI: 16.1-21.6%), ARMD (12.07%, 95% CI: 10.0-14.5%), and central retinal vein occlusion (CRVO, 11.08%, 95% CI: 9.1-13.4%). Demographic analysis revealed a male predominance (73.65%, 95% CI: 70.5-76.6%) and a younger population (60.3% ≤60 years, 95% CI: 56.9-63.6%). Comorbidities were highly prevalent, with diabetes mellitus (69.83%, 95% CI: 66.6-72.9%) and hypertension (58.99%, 95% CI: 55.6-62.3%) being the most common. Clinical evaluation showed decreased vision as the primary symptom (97.17%, 95% CI: 95.8-98.1%). Best Corrected Visual Acuity (BCVA) of 0.5 or better was observed in 52.1% of patients (95% CI: 48.7-55.5%). Optical Coherence Tomography revealed Central Macular Thickness exceeding 300 µm in 34.62% of cases (95% CI: 31.4-37.9%). Laser therapy was the predominant treatment modality (11.13%, 95% CI: 9.2-13.4%). Follow-up adherence demonstrated a significant decline after the initial visit (from 76.13% to 16.77%, p<0.001). Conclusion: This study highlights the urgent need for enhanced screening protocols and multidisciplinary management strategies in Eastern India to address the high burden of retinal diseases. Targeted interventions in this region could prevent vision loss and improve healthcare outcomes.